A mixed-integer linear programming approach for optimal type, size and allocation of distributed generation in radial distribution systems - Rueda-Medina, Augusto C. [UNESP]; Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Padilha-Feltrin, Antonio [UNESP]; Romero, Rubén [UNESP] (Elsevier, 2013)
This paper presents a mixed-integer linear programming approach to solving the problem of optimal type, size and allocation of distributed generators (DGs) in radial distribution systems. In the proposed formulation, (a) the steady-state operation of the radial distribution system, considering different load levels, is modeled through linear expressions; (b) different types of DGs are represented by their capability curves; (c) the short-circuit current capacity of the circuits is modeled through linear expressions; and (d) different topologies of the radial distribution system are considered. The objective function minimizes the annualized investment and operation costs. The use of a mixed-integer linear formulation guarantees convergence to optimality using existing optimization software. The results of one test system are presented in order to show the accuracy as well as the efficiency of the proposed solution technique.© 2012 Elsevier B.V. All rights reserved.
Keywords: Distributed generation; Mixed-integer linear programming; Optimal allocation; Radial distribution system; Short-circuit currents; Capability curves; Distributed generators; Linear expression; Linear formulation; Load levels; Mixed integer linear programming; Mixed-integer; Objective functions; Operation cost; Optimality; Optimization software; Radial distribution systems; Solution techniques; Steady-state operation; Test systems; Distributed power generation; Integer programming; Optimization; Local area networks